Transformations and Reforms of European Health Care Systems: The Case of Estonia - Suchecka, Jadwiga (Comparative Economic Research. Central and Eastern Europe, 2014)
The purpose of this article is to present the main directions of changes in the Estonian health care system following the transformation of the national economy and the accession of Estonia to the European Union. Special attention has been paid to the ways of sourcing, and the collection and redistribution of financial resources allocated to health care in different periods of the transformation. The initial changes introduced far-reaching decentralization of the health system, while further reforms led to his re-centralization. The intensity of the re-centralization of finance and health management processes was accelerated after 2008, when the impact of the global financial crisis on the condition of the economy of Estonia was significant. As a result of the introduced changes, Bismarck’s mixed system – a hybrid system – has been formed.